ANALISA STRUKTUR BOX GIRDER JALAN LAYANG KERETA API KUALANAMU - Kamaluddin Lubis; Muhammad Ridwan (Portal: Jurnal Teknik Sipil, 2017)
The development of prestressed concrete is growing rapidly as the widespread construction technology. The use of prestressed concrete supports infrastructure development in Indonesia , especially Kualanamu Railway overpass in the city of Medan that use Box Girder with sectional height 2400 mm as a structural component . The case study of prestressed concrete box girder Railway flyover with spans of 40 meters Kualanamu explain sectional effectiveness girders whereare internaltendons filled in strand steel cables. 12.7 mm totaling 60 pieces. Further analyzing the percentage loss of prestressing force that occurs in the tendon due to the shortening of the elastic, friction on the tendon , creep , shrinkage of the concrete and so on. Additionally introduced step by step production process prestressed concrete box girder ranging from reinforcement to casting in the precast concrete plant.Keywords: Prestressed concrete , box girder, loss of prestressed